2016
DOI: 10.1186/s12879-016-2078-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of medically attended influenza among residents of Shai-Osudoku and Ningo-Prampram Districts, Ghana, May 2013 – April 2015

Abstract: BackgroundInfluenza vaccination is recommended by the World Health Organization for high risk groups, yet few data exist on influenza disease burden in West Africa.MethodsWe estimated medically attended influenza-associated illness rates among residents of Shai-Osudoku and Ningo Pram-Pram Districts (SONPD), Ghana. From May 2013 to April 2015, we conducted prospective surveillance for severe acute respiratory illness (SARI) and influenza-like illness (ILI) in 17 health facilities. In 2015, we conducted a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
37
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 12 publications
15
37
2
Order By: Relevance
“…This was observed also in other studies conducted in Africa 19, 20, 21. Our estimates of influenza‐associated SARI hospitalization in individuals aged ≥5 years are on the lower end, but overall similar to other estimates from Africa (22 per 100 000 population in South Africa 21 and 30 per 100 000 population in Kenya 20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was observed also in other studies conducted in Africa 19, 20, 21. Our estimates of influenza‐associated SARI hospitalization in individuals aged ≥5 years are on the lower end, but overall similar to other estimates from Africa (22 per 100 000 population in South Africa 21 and 30 per 100 000 population in Kenya 20).…”
Section: Discussionsupporting
confidence: 90%
“…The influenza virus detection rate may vary in different locations in Zambia; however, this could not be investigated. Nonetheless, the influenza virus detection rate among SARI cases was found to be similar across 15 African countries including Zambia (median: 8.9%; interquartile range: 5.7%‐11.6%),4 and our rates of SARI and influenza‐associated SARI hospitalizations were similar to those obtained from population‐based surveillance in other African countries 19, 20, 21. In addition, we used bootstrapping for the calculation of the CIs to account for the level of uncertainty associated with all adjustments used in our estimation approach as previously reported 14, 15.…”
Section: Discussionsupporting
confidence: 69%
“…Due to differences in surveillance systems, case definitions, access to care and healthcare‐seeking behaviour, direct comparisons of the incidence rates are not possible; however, similar trends were observed. As in previous reports,16, 17 the incidence of SARI was higher among younger (<16 years old) than older cases (≥16 years old) except for 2015/16 season, a season dominated by A(H1N1)pdm09 when the incidence of SARI was higher in the older cases (≥16 years old). The incidence of influenza‐associated SARI was similar between the age groups for all seasons except 2011/2012, when the rate in the <16‐year‐old group was 4 times higher than the older group.…”
Section: Discussionsupporting
confidence: 83%
“…As such, we do not consider the mortality estimates (6‐11 per 100 000 population) in Bangladesh to be high when compared to other countries; however, we do consider 6‐11 deaths per 100 000 population to be a substantial burden for the country of Bangladesh. Similarly, the estimated influenza‐associated hospitalization rates in Rwanda (34 per 100 000 population) are comparable to those of other African countries situated in equatorial, tropical, and subtropical regions: 21 (95% CI: 19‐23) per 100 000 population in Kenya,8 30 (95% CI: 13‐84) per 100 000 population in Ghana,9 30 (95% CI: 24‐36) per 100 000 population in Madagascar,10 45 (95% CI: 41‐49) per 100 000 population in South Africa,11 and 44 (95% CI: 31‐57) per 100 000 population in Zambia 12. In addition, a global study reported the highest rates of influenza‐associated hospitalization among African children followed by South‐East Asia and the Western Pacific 13.…”
mentioning
confidence: 53%
“…To address this, an analysis exploring the effect of respiratory syncytial virus (RSV) circulation on ARI deaths among children <5 years of age in Bangladesh is underway and similar studies could be conducted in Rwanda. Nonetheless, the estimated influenza‐associated hospitalization rates among children aged <5 years in Rwanda (168 per 100 000 population)3 are similar to those of South Africa (156 per 100 000 population),11 other countries in Africa,8, 9, 12 and global estimates for Africa (174 per 100 000 population) 13. Whereas the circulation patterns of RSV are poorly understood in Rwanda and other African countries, in South Africa, the RSV season precedes and minimally overlaps with the influenza season 24.…”
mentioning
confidence: 80%